Pedagogias com as juventudes : o instituto federal no andarilhar por uma educação libertadora - Giovenardi, Maíra (2023)
The plural conception contained in the youth category denotes the multiple ways of being young, as their demands, needs and identities are multifaceted, expressing the singularities that characterize this social segment, considering its heterogeneity, beyond the age range. In this perspective, this study presents as a general objective, to build and enhance methodologies that contribute to the strengthening of processes of autonomy, participation and protagonism of young students. The theoretical perspective that supported this research was Freire‟s epistemology which guided the methodology, of participatory and dialogic nature, based on love, that promoted the students to actively engage by suggesting themes and ways of discussion. This was a participatory and qualitative research that followed the Dialectical-Critical Method and articulated categories like: historicity, wholeness and contradiction. This study had its empirical locus developed in an Instituto Federal de Educação [Federal College] where technical high school and college students, as well as the educational managers participated. Empirical data was collected through three semi structured interviews with the educational managers of the College and the focus groups formed by students, with an average of 15 participants per group, all these steps performed in online modality. The documental research emphasized institutional documents, such as resolutions, normative documents, curriculum, management reports and the pedagogical project of a course. Participative observation and a field report are also part of this study. Data analysis followed Moraes‟s (1999) content analysis. Data collection happened during the pandemic of COVID-19, from 2020 to 2021. Results point that there are two projects in the educational system: the first, centered in satisfying the interests of the capitalist society, the “banking concept of education” (FREIRE, 2019a), that keeps current order; the second, guided by the respect of the subjects‟ autonomy through a democratic and liberating education, that emancipates the citizens attending people‟s demands, the “education that liberates” (FREIRE, 2019a). All social segments are affected by these projects, especially the youths, which demands Public Politics attention, mainly on Educational Policies. Thus, the focus groups guided by participating methodologies with the students acted as a support network based on empathy, dialogue, like an appointment for hope, an opportunity for being curious and exercising citizenship. Finally, educational spaces constitute a possibility for dialogue with young people, not only inside the walls of the school, but in the outside too, that must understand the plurality and potentiality of youths, shattering the “adultcentric” and silencing culture, encouraging and potentializing their speech, ideas, values and feelings, strengthening autonomy processes, the participation and protagonism of youths in society.